Capitalism, socialism and state interventionism: system-related controversies over East Asian model of development (Economic and Political Thought, 2018)
The East Asian development model, as a result of which some Asian economieshave achieved spectacular developmental results, is based on the concept ofa developmental state. The developmental state is characterized by specific systemicand institutional arrangements. In principle, it functions in the conditions ofthe capitalist system (socialism is not able to generate adequate growth dynamicsin the long term); nevertheless, the authorities apply central planning mechanismsto implement their development strategy. Thus, state interventionism plays animportant developmental role, although it is not intended to ensure social cohesion.
Keywords: East Asia, development, capitalism, socialism, interventionism